PENGEMBANGAN LEMBAR KERJA SISWA (LKS) DENGAN MODEL PROBLEM BASED LEARNING (PBL) DIPADU THINK PAIR SHARE (TPS) - Palura, Frans Tunggu; Widyaningrum, Diyah Ayu (Edubiotik : Jurnal Pendidikan, Biologi dan Terapan, 2017)
This study aims to produce LKS based on problem based learning coupled think pair share and can be applied in teaching and learning process, describe the implementation of learning, the level of legibility of students after using LKS based prbolem based learning combined think pair share. This research is a development research using 4-D development model that is Define (Define), Design (Design), Develop (Development), while Disseminate stage (Dissemination) is not done due to time constraint. The pilot phase was conducted at SMA Negeri 1 Kambera in class XI-IPA which amounted to 8 students. The results showed that in accordance with the study of LKS, the worksheet of students based on problem based learning combined think pair share process that has been developed declared eligible for trial. Implementation of learning using LKS has reached / obtained the average implementation of% The level of legality of LKS based on problem based learning combined think pair share of students obtain the overall average of 3.87% stated in the category Very Worthy, it shows that most Students argue the material and media used are easy to understand and the appearance of student worksheets (LKS) interesting.